52 A virtual multidisciplinary journal club. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Stanley, Sarah; Bonwick, Helen; Chapman, Laura; Nwosu, Amara
Abstract : Background: Research is essential in enabling practitioners to deliver evidence-based treatment and care. 1 A journal club has been identified as a way to encourage a research culture by engaging staff to build evidence of best practice. 2 Since January 2019 Marie Curie Hospice Liverpool have developed a unique multi-disciplinary approach to journal club, which has recently been impacted by the COVID19 pandemic. We recognised the importance of re-instating these sessions in order to continue learning and development of a research culture in our hospice. Methods: Our journal club is held fortnightly and is co-ordinated by the research nurse and speciality doctor with support from our research lead. Following the height of the COVID19 pandemic, meetings resumed and were encouraged to utilise Microsoft teams in order to maintain social distancing in meeting rooms. This provided us with a unique opportunity to expand our journal club outside of the hospice and invite healthcare professionals from external organisations (including acute hospital trusts and other local hospices) to join these meetings. Results: To date we have held a total of 22 meetings. Healthcare professionals attending the meetings have generated 109 research questions relevant to palliative care. Feedback from external organisations has been positive, and these healthcare professionals report being grateful for the opportunity to attend a journal club. We are currently working on developing a structure for a quality improvement project which will allow members of the MDT to come together and answer one of our generated questions. Conclusions: Our MDT journal club model has proved to be successful, and with the support of technology has allowed us to share our learning outside of the hospice. Attendance and engagement across disciplines has made our staff research aware, creating a culture of enquiry and an eagerness to provide evidence-based care. References: Preston NJ, Payne SA and Todd C. Conducting research in palliative care patients: burden or an opportunity? International journal of Palliative Nursing 2009;15 (11):524–525. Payne S, Preston N, Turner M, Rolls L. Research in palliative care - can hospices afford to not be involved? International Observatory on End of Life Care 2013.